Distribution of Dengue Serotypes in Argentina in the Last 2 Years - Araujo, Mercedes Pablo; Carnovale, Susana (Multidisciplinar (Montevideo), 2025)
Introduction: dengue virus is transmitted mainly by the Aedes aegypti mosquito, and represents a public health problem worldwide, especially in tropical and subtropical regions. Objective: to determine the dengue serotypes circulating in Argentina.Methods: Epidemiological reports were evaluated retrospectively. Dengue surveillance data from the National Ministry of Health of the Argentine Republic during the period 2022 to 2024 were used for this purpose. Results: the serotypes circulating in Argentina during 2022-2023 were DenV-1 and DenV-2; during the 2024 outbreak, the DenV-3 serotype was introduced, with DenV-2 accounting for 57,41 %, DenV-1 for 42,40 % and DenV-3 for 0,19 %. Conclusion: the predominance of serotypes DENV-1 and DENV-2, and the introduction of serotype DENV-3 in 2024, increase the risk of sequential infections and severe forms of the disease, which emphasizes the need to implement effective strategies, between endemic and epidemic years, for vector control and to promote community awareness